Optimalisasi Peran Guru Pengabdian Untuk Meningkatkan Kualitas Pembelajaran di Pondok Pesantren Al-Amanah Al-Gontory: Sebuah Tinjauan Efektivitas - Dita Anggraini; Akhmad Shunhaji; Syamsul Bahri Tanrere (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
Teacher effectiveness is the act of displaying or carrying out an activity within an educational institution. Effective teachers must have an important role in dedicating themselves to the educational process. The primary objective of this study is to delineate endeavors aimed at enhancing the efficacy of service teachers in elevating the standard of learning. The research adopts a qualitative approach employing thematic analysis as its model. The data collection methodologies encompass interviews, observations, and documentation. The findings reveal that the predominant model for nurturing service teachers at the Al-Amanah Al-Gontory Islamic boarding school is centered around total quality control. This entails overseeing and regulating the quality of the entire life structure, thereby influencing various facets of the educational environment. The methods used include direction, training, assignment, habituation, supervision, uswah hasanah, and approaches (humane, program, idealism). Next, enhancing teacher proficiency involves the implementation of various programs such as creating pre-teaching materials (RPP), reinforcing teaching materials, reviewing learning materials (Taftisyu al-I'dat al-mufaaji'), conducting supervision (Naqdu Tadris), and carrying out weekly assessments commonly referred to as Saturday evaluations. The effectiveness of the learning experience is validated through the continual commitment of the teaching staff.